DIFFERENTIAL DIAGNOSIS OF PROGENIC FORMS OF BITE AND ITS IMPORTANCE IN PREDICTING THE RESULTS OF ORTHODONTIC TREATMENT - P.S. Flis; K.V. Storozhenko (Ukrainian Medical Stomatological Academy, 2016)
Increased requirements of patients to the results of orthodontic treatment are forcing orthodontists to have a deep knowledge of the anatomy of the face, to know the structure and constituent elements of facial harmony, guided in species proportions and variations of structure of the facial skull. Growth, according to S. Williams (2006), is an important criterion for differential diagnosis and treatment of the pathology of occlusion. Because most patients are growing in the treatment process, orthodontists become vital to know the principles of growth, as well as the biological essence of the occlusion. Therefore, the definition of individual genetic profile and growth type of the jaws is a key point in diagnosis, predicting the results of orthodontic treatment and the preparation of a rational treatment plan. In the literature these issues are still insufficiently lit, which was the subject of our studies. The purpose of the study: to improve the differential diagnosis of progenic forms of bite and predicting the results of orthodontic treatment for patients of all ages. Materials and methods. We transcribed lateral cephalograms of 53 patients with progenic forms of bite aged from 12 to 35 years. Analysis of cephalograms was conducted by the method of A.M. Schwarz and J. Jarabak with measurement data comparison. Cephalometric analysis by A.M. Schwarz included determination of craniometry, gnathometry and profile analyzing data. Particular attention was paid to the determination of individual genetic profile of face in every patient with progenic bite. To determine the type of growth we used a method proposed by J. Jarabak (Fig.2). Special attention was paid to determination growth type such as: horizontal, vertical and neutral. Depending on the magnitude of the sum angle, the patients were divided into three groups: the first group included 25 patients with a horizontal type of growth, the second one 18 patients with a vertical type of growth and the third group 10 patients - with neutral type of growth. Comparative analysis of cephalograms by A. M. Schwarz and J. Jarabak allowed conducting more detailed differential diagnosis of progenics forms of bite and creating an algorithm of its implementation, which can help diagnose and make a rational treatment plan and predict its result. Conclusions • Differential diagnosis of progenic forms of bite according to our developed algorithm allows making diagnose more objectively, choosing a rational method of orthodontic treatment and predicting its result. • Crucial importance in predicting the results of orthodontic treatment is the determination of individual genetic profile of face and the type of growth of the facial skull, especially in patients with progenic forms of bite. • The most unfavorable individual genetic profile of face in terms of prediction of orthodontic treatment is retroface with forward sloping chin. • The size of the jaws and the position in the skull plays an important role in the preparation of a rational plan of orthodontic treatment. • Analysis of the lateral cephalograms allows providing differentiated approach for the diagnosis of progenic forms of bite.